Direct oxidation of H-2 to H2O2 over Br and F-promoted Pd/Al2O3 in aqueous acidic medium: influence of the concentration of Br and F and the method of incorporation of the two halogens in the catalyst on their beneficial synergetic effect on the net H2O2 - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2007)
Influence of the addition of F (0-1.1 mmol/g) in the pre-brominated Pd/Al2O3 (Br loading = 0.13 mmol/g) and also that of Br (0.13 mmol/g) in the pre-fluorinated Pd/Al2O3 (F loading = 0.53 mmol/g) on the net H2O2 formation in the H-2-to-H2O2 oxidation (with H-2/O-2 mole ratio of 1.0) over the halogenated catalysts in aqueous acidic (0.1 M H3PO4) medium have been investigated. In both the cases, the highest synergetic effect (resulting in the highest net H2O2 formation) produced by the addition of other halogen is observed at its optimum concentration (viz. 0.13 mmol Br/g in the fluorinated Pd/Al2O3 and 0.13 mmol F/g in the pre-brominated Pd/Al2O3). The beneficial synergetic effect of the two halogens is also found to be strongly influenced by the way of incorporation of the two halogens in the catalyst. The enhancement in the net rate of H2O2 formation due to the synergetic effect for the different methods of Pd/Al2O3 halogenation is in the following order: simultaneous bromination and fluorination < first fluorination and then bromination < first bromination and then fluorination. The fluorination (at optimum concentration of 0.13 mmol F/g) of the pre-brominated (0.13 mmol Br/g) Pd/Al2O3 led to the best catalyst for the H-2-to-H2O2 oxidation with 100% H-2 conversion and 78% H2O2 yield/selectivity. The destruction of H2O2 by its decomposition and/or hydrogenation over the halogenated catalysts has also been studied. (c) 2007 Published by Elsevier B.V.
Keywords: F and Br-promoted Pd/Al2O3; Hydrogen peroxide; oxidation of H-2-to-H2O2; synergetic effect of F and Br